Seed-Borne Fungi Associated With Pepper (Capsicum Species) in Some States in Nigeria. - Otusanya, M. O. (European Journal of Applied Sciences, 2022)
Capsicum (Pepper: common name) species fruits are ground and utilized either fresh or dried as an essential ingredient of sauce/soup in every region of Nigeria. Seed health tests were carried out on thirty-one seed cultivars of Capsicum that is Capsicum frutescens L. and Capsicum annuum L. from Kaduna, Benue and Oyo States in Nigeria in this study. An initial mini-greenhouse project with some of the cultivars resulted in Curly-top Virus symptoms disease. The latter disease which had not been hitherto reported in Nigerian Capsicum cultivars necessitated the grouping of the seeds into two sets of Nigerian/Indigenous Cultivars (in group one) and Exotic plus less exotic cultivars in a second group. The Nigerian set made up of eight cultivars was examined with and without surface-sterilization for mycoflora. The design was completely randomized comprising five (5), replicates per cultivar and 50 seeds in a cultivar replicate. The working sample was 250 seeds per cultivar set up under an alternating cycle of 12hours Near ultra-violet light (NUV light) and 12hours darkness in an incubating room of 27 ± 2oC temperature. Incubation for viability counts and associated fungi was for seven days. The Exotic plus less exotic set had twenty-three cultivars, which were tested as the Nigerian Cultivars, without surface-sterilization. Viability was over 30.00% only in eleven of the twenty-three Exotic plus less exotic Cultivars, whereas there was none (over 30%) in the indigenous or Nigerian Cultivar set. Three reasons adduced for the low turn-out in germination are period of seed storage of six months or over, lack of seed treatment and mixed infections possibly with viruses or nematodes. The genera Phoma, Chaetomium, Penicillium, Rhizopus and Cladosporium with the former two associated with all eight cultivars, were isolated from the un-sterilized indigenous/Nigerian set and are considered to be surface contaminants. Twenty fungi namely Aspergillus flavus, A. niger, A. ochraceus, A. wentii, Cercospora sp., Chaetomium sp., Colletotrichum sp., Curvalaria lunata, C. pallescens, Fusarium equiseti, F. moniliforme, F. solani, Graphuinu sp., Macrophomina sp., Penicillium sp., Phoma sp., Rhizopus sp., Spegazzima sp., Stemphylium sp. and Verticillium sp. were isolated from the un-sterillized Exotic plus less exotic cultivars set. Among the twenty, Aspergillus flavus, Fusarium moniliforme and Phoma sp. were dominant as they were associated with 22, 21 and 19 of the twenty-three cultivars respectively. Overall mean infection of 13.55%, 8.06% and 5.23% were highest by A. flavus, Colletotrichum sp. and Rhizopus sp. respectively and the three highest cultivar replicate infections were 55.60%, 32.80% and 23.20% also by Aspergillus flavus, Rhizopus sp. and Colletotrichum sp. in that order respectively. Seed-borne saprophytes are reported to be economically important as they effect seed rot, seed weight loss or seed germination reduction and ought to be excluded by adequate seed treatment. Twelve fungi were associated and isolated from the eight surface-sterilized Indigenous/Nigerian cultivar set. They are Aspergillus flavus, A. niger, A. tamari, Cochliobolus lunatus, Colletotrichum capsici, Corynespora casiicola, Curunlaria pallescens, Fusarium moniliforme, F. pallidoroseum, Macrophomina phaseolina, Pithomyces chartarum and Thielavia terricola. Aspergillus flavus, Fusarium moniliforme and Aspergillus niger were the three most frequently occurring/dominant fungi as they were isolated from all eight, seven and six cultivars respectively. However, overall mean infection was highest by Aspergillus flavus 11.80%, second is Colletotrichum capsici 6.60% and third is Fusarium moniliforme 3.20%. The two highest infections in any cultivar replicate also were 55.60% by Aspergillus flavus and 23.20% by Colletotrichum capsici, and in third place is 15.20% by Aspergillus niger. Colletotrichum capsici and two other Colletotrichum species gloeosporioides and acutatum are known to be the most important economic fungal pathogens of Capsicum species in Nigeria and globally causing ripe fruit rot and stem die-back. Seed-borne Fusarium species namely moniliforme, solani and oxysporum and Verticillium species also contribute to high pre-harvest losses (by damping-off of seedlings and witling of field plants) on Pepper globally. The Aspergilli cause moulds on above-ground portions of pepper plants and Macrophomina is known to be parasitic on leaves. Pithomyces chartarum and Thielavia terricola have not been reported on Capsicum species and are therefore new records on Capsicum seeds in Nigeria. Seed storage for planting without adequate/appropriate seed treatment is to be discouraged in Nigeria; because of low viability as in this study, and seedling failure/field epidemics/crop failure. Fundings and extensive trials with Plant extracts, Oils and Biocontrol microbes should also be underscored as necessary for seed treatment in place of fungicides for health and environmental safety. Improved Seeds should also be sought for as priority from approved Agencies/Seed Companies by farmers.